Social Dimensions of Sustainable Development in International Public Opinion - Rydzewski, Paweł (Problemy Ekorozwoju, 2019)
The article examines opinions on various elements of the social pillar of sustainable development. The analysis is based on the ISSP Role of Government V (2016). The research sample consisted of over 35,600 respondents from 28 different countries. It has been assumed that the most important indicator is the opinion that a given element requires much more government spending than it receives now. From the point of view of public opinion, health and education seem to constitute the crucial elements of the social pillar of sustainable development, whereas security and especially culture and the arts are much less important.